Parental Influences on Health and Longevity: Lessons from a Large Sample of Adoptees - Mikael Lindahl; Evelina Lundberg; Mårten Palme; Emilia Simeonova (Institute for the Study of Labor (IZA), 2016)
To what extent is the length of our lives determined by pre-birth factors? And to what extent is it affected by parental resources during our upbringing that can be influenced by public policy? We study the formation of adult health and mortality using data on about 21,000 adoptees born between 1940 and 1967. The data include detailed information on both biological and adopting parents. We find that the health of the biological parents affects the health of their adopted children. Thus, we confirm that genes and conditions in utero are important intergenerational transmission channels for long-term health. However, we also find strong evidence that the educational attainment of the adopting mother has a significant impact on the health of her adoptive children, suggesting that family environment and resources in the post-birth years have long-term consequences for children's health.
Keywords: I10; I14; I24; 330; health inequality; mortality; pre- versus post-birth decomposition